Linking Budget and Policies: The Case of Ivory Coast - Kanyamuna, Vincent (Advances in Social Sciences Research Journal, 2022)
In the case of Ivory Coast, some budgetary reforms have been implemented since 1999 in order to improve the budget allocation and ensure a better translation of development strategies into budget. Unfortunately, taking into account national strategies and policies have not always been the main preoccupation during budgeting. However, the requirements of managing for results bring the fiscal authorities to pay particular attention to the establishment of the link between policies and budgets. Moreover, establishing this link between policies and budget is becoming a major issue since the West African Economic Monetary Union (WAEMU) adopted in 2009 new budgetary reforms to promote performance budgeting. So, this study addresses the issue of linking policies and budgets in the specific case of Ivory Coast. To that end, it focuses on the existing gaps between the budgeting process and policies through the Poverty Reduction Strategy Papers (PRSPs) or simply the National Development Plans (NDPs). The analysis of the current budgeting process shows that the budgeting is not based on the PRSPs and sectoral plans; the integration between planning and budgeting is low, the budgeting is done through a resource-based approach and the medium and long-term budgeting is not established. Moreover, the Parliament has not been involved in the budget process and PRSP elaboration especially in the last years. Only the civil society has been involved in the PRSP elaboration but they are not consulted during the budget process. Therefore, attention should be given to the challenges related to strategic planning, management style and actors to be involved. This must be done through (i) the drafting of sectoral plans based on the NDPs/PRSPs; (ii) the integration between planning and budgeting; (iii) the introduction of a strategic phase and a medium-term perspective to the budget process; (iv) the shifting from a resource-based to a results-based approach; (v) the increase of the involvement of parliament and civil society in the budget process. Further, the MTEF process that started in 2010 should be reinforced through the completion of a Macro-economic framework and a Medium Term Budgetary Framework, a national MTEF to give the ceilings on expenditure to line ministries for a medium and long-term view in order to establish their sectoral MTEFs. Moreover, the public financial management reforms should continue in order to reinforce the budget credibility which is essential in the establishment of good and reliable MTEFs.